Association Analysis of Stem Solidness and Wheat Stem Sawfly Resistance in a Panel of North American Spring Wheat Germplasm. Issue 5 (1st September 2015) - Varella, A. C.; Weaver, D. K.; Sherman, J. D.; Blake, N. K.; Heo, H. Y.; Kalous, J. R.; Chao, S.; Hofland, M. L.; Martin, J. M.; Kephart, K. D.; Talbert, L. E.
ABSTRACT: The expanding geographical range of wheat stem sawfly (WSS) damage, coupled with the limited number of effective control measures, calls for a need to better characterize and explore the genetic variability for resistance in wheat ( Triticum aestivum L.) germplasm from North America. An association‐mapping analysis for stem solidness and wheat stem sawfly resistance was conducted using a set of 244 elite spring wheat lines from 10 North American breeding programs. Three previously identified quantitative trait loci (QTL) for resistance were confirmed, including QTL for stem solidness, heading date, and stem cutting. Three new QTL on chromosomes 2A, 3A, and 5B were identified to be associated with larval mortality and a QTL associated with early stem solidness was identified on chromosome 5D. Genetic variation for late stem solidness is mainly determined by the solid‐stem QTL on chromosome 3B, while variation for early solidness is affected by chromosomal regions on 1B, 3B, and 5D. Potential sources of a novel resistance mechanism causing larval mortality were identified among the panel lines. Favorable alleles for stem solidness and other resistance traits are available within North American wheat germplasm, but only Montana and South Dakota breeding programs appear to have favorable alleles for all QTLs detected in this study. Improvements in wheat stem sawfly management, for both historically impacted areas and for regions first experiencing damage, may be obtained using alleles that already exist in elite germplasm.